Exploring the effect of use contexts on user engagement toward tourism short video platforms - Fei Qu; Nian Wang; Xianyan Zhang; Lan Wang (Frontiers in Psychology, 2022)
With tourism short video platforms’ increasingly fierce competition, retaining existing users and improving engagement has taken on greater theoretical and practical significance. Based on the self-system model of motivational development, this study, involving an empirical analysis of 252 user data samples, establishes a research model to determine how the use contexts affect users’ psychological process and finally lead to behavioral engagement. In particular, four use contexts of tourism short video platforms are proposed—namely, information acquisition, leisure and entertainment, attention obtainment, and social interaction. Different use contexts differ in the degree to which they satisfy users’ three psychological needs, thus influence their attitudinal engagement and behavioral engagement. The research results can provide theoretical and practical references on how to improve user engagement toward tourism short video platforms.